PENGARUH PENERAPAN MEDIA 3D PRINTING TERHADAP MINAT DAN HASIL BELAJAR PESERTA DIDIK PADA MATERI SISTEM EKSKRESI - Al Anshori, Fitrah; Syam, Sukmawati; Alfat, Nurul (Universitas Cokroaminoto Palopo, 2024)
This research aims to determine the effect of applying 3D Printing media on student interest and learning outcomes in the Excretory System material. The type of research used was pre-experimental with a One Group Pretest Posttest Design. The population of class XI students at SMA Negeri 7 Luwu was 153 students and the sample used was 32 class XI MIPA 4 students. The sampling technique was purposive sampling. The instruments used in the research were learning outcomes tests and questionnaires. Research data were analyzed using descriptive statistics and inferential statistics and hypothesis testing using the t-test. The research results show that: (1) the learning interest of students who are taught using 3D printing media is 64.41 (medium); (2) The learning outcomes of students taught using 3D printing media have an average value of 89.50 (very high); (3) The results of the hypothesis test on students' learning interest obtained a sig value. 0.00<0.05 which means H0 is rejected and H1 is accepted; (4) The results of the t-test on student learning outcomes obtained a sig value. 0.00<0.05 which means H0 is rejected and H1 is accepted. Based on this explanation, it was concluded that there was an influence of the application of 3D Printing media on interest and learning outcomes in the Excretory System material.